UTA Method for Sustainable Decisions in Ceramic Tile Production - KAÇAR, YAREN; BİÇER, SENA İREM; FİLİZ, AYBERK; DURMUŞ, EMİNE ŞEYMA; KUŞ, DUYGU; GERGİN, ZEYNEP (Springer Science and Business Media Deutschland GmbH, 2025)
Efforts to minimize environmental damage have gained global importance due to critical issues such as climate change and the depletion of natural resources. In this context, manufacturing industries have increasingly prioritized environmental protection goals alongside profitability when planning their operations. With growing customer awareness and regulatory pressures, such as EU directives and governmental regulations, a focus on sustainability has become both a competitive advantage and a necessity. Consequently, companies are adopting sustainability-oriented approaches, including environmentally friendly material selection from raw materials to packaging. This trend toward sustainability-oriented production planning is also evident in the ceramic industry, the focus of this study. The main raw materials for ceramic products—clay, quartz, and feldspar—are extracted from mines, but their supply is becoming increasingly difficult and costly due to dwindling natural resources. As a result, sustainability-driven competition in the sector has prompted companies to seek more sustainable alternatives for these natural materials. This study aims to assist a manufacturing company in the ceramic sector with its sustainability-focused raw material selection process. The study's objective is to identify production recipes that minimize costs while using sustainable raw materials for floor tile production. The Utility Additive (UTA) multi-criteria decision-making (MCDM) method is applied to evaluate alternative recipes. These recipes incorporate environmentally friendly raw materials, such as recycled products and wastewater. Twelve criteria are initially identified and categorized under sustainability, cost, and manufacturability to guide the decision-making process. The UTA method is then used to determine the order of preference for five different recipes, and two scenarios are evaluated based on changes in the weights of the decision criteria.
International Symposium for Production Research
Part of the book series: Lecture Notes in Mechanical Engineering ((LNME)).
Keywords: Ceramic production; MCDM; Sustainability; Sustainable material selection; UTA